A macromolecular halogen‐free flame retardant and its effect on the properties of thermoplastic polyesters. (1st October 2018) - Adner, David; Helmy, Mina; Otto, Tobias; Schellenberg, Jürgen; Schadewald, Anke
Summary: A halogen‐free flame retardant with a macromolecular structure is presented. Its synthesis proceeds via polymerization of phosphorus‐containing acrylate monomers. The flame retardant was incorporated into poly(ethylene terephthalate) by extrusion. Samples with different concentrations (0.5, 2.5, and 5.0 wt%) as well as a 25 wt% masterbatch were prepared. All samples were transparent and colorless without any visible irregularities. Thermal investigations reveal an unchanged glass transition temperature. Tensile tests show the typical mechanical behavior of poly(ethylene terephthalate), but with an elevated Young's modulus. The burning behavior was investigated by several small‐flame tests in vertical and horizontal orientation, as well as by cone calorimetry. It is shown that samples with 2.5 wt% flame retardant pass the vertical UL94 test (V‐2, 20‐mm flame). The sample cannot be ignited in the horizontal fire test according to FMVSS 302. The oxygen index was measured to 28 vol%. Cone calorimetric measurements show that the effective heat of combustion as well as the total heat evolved is reduced.